Fuzzy EOQ model of a high technology product under trial-repeat purchase demand criterion. (3rd July 2018) - Chanda, Udayan; Kumar, Alok; Kumar Das, Jitendra
Abstract: Accurate prediction and knowledge of adoption pattern is critical to formulate inventory strategies for any technology product. Prior researches in this area recommended that aggregate level demand models often forecast imprecise sales figure. We argue that it is essential to recognize the technology specific adoption dynamics prior to formulate the inventory strategies. This paper aims to develop an Economic Order Quantity (EOQ) model to find strategy for a firm that sells technology products' over a defined planning horizon. Demand is considered to follow trial-repeat purchase phenomenon. The fuzzy criterion is incorporated to address the problems of uncertain nature of marketing parameters. The model is illustrated with a numerical example and a comprehensive sensitivity analysis on the optimal solution with respect to different parameters has also been performed.